Long-term, sustainable solutions to radioactive waste management - Kristina Kvashnina; Francis Claret; Nicolas Clavier; Tatiana G. Levitskaia; Haruko Wainwright; Tiankai Yao (Scientific Reports, 2024)
Abstract Nuclear power plays a pivotal role in ensuring a scalable, affordable, and reliable low-carbon electricity supply. Along with other low-carbon energy technologies, nuclear energy is essential for reducing our reliance on fossil fuels, addressing climate change and air pollution, and achieving a sustainable economy. Whilst significant progress has been made in reducing the volume of final radioactive waste, its management remains one of the most important challenges when considering the continued use and expansion of nuclear energy. This recently published collection highlights the latest technological and scientific advances aimed to improve the safe, long-term, and sustainable management of wastes produced from nuclear power generation.